Improving Spatial Thinking Skills Through A Digital Interactive Learning Platform Based on Google Sites - Ardiansyah, Alen; Prasetyo, Ketut; Rindawati, Rindawati (Jurnal Pendidikan : Riset dan Konseptual, 2025)
Abstract: Spatial thinking ability has a fundamental role in geographical understanding, yet it is often neglected in educational curriculum. This study aims to explore the effectiveness of the Google Sites platform in improving the spatial thinking skills of students in class VIII SMP Negeri 48 Surabaya. The research used a quasi-experimental design with a nonequivalent control group design approach, involving 34 students in experimental and control classes. The research instruments included media validation, material validation, student response questionnaire, and spatial thinking ability test based on eight indicators: comparison, aura, region, hierarchy, transition, analogy, pattern, and association. Data analysis was conducted through an independent sample t-test with a significance criterion of p < 0.05. The results showed a significant difference with an asymp.sig (2-tailed) coefficient of 0.000, proving an increase in spatial thinking ability. The percentage of students in the high category increased from 35% to 50%, while 76% of students rated the Google Sites platform as influential in developing spatial thinking skills. This research confirms the potential of digital platforms in transforming the learning process and developing complex thinking skills.